JAVANESE IDENTITY THROUGH SYMBOLIZATION OF CANTING: A STUDY OF THE NOVEL CANTING BY ARSWENDO ATMOWILOTO - Wahyu Handayani Setyaningsih; Wury Dwiwardani (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
This research takes novel Canting as the object of analysis. This research used cultural semiotics approach. The research aims to find the Javanese identity symbolized in canting. The results obtained as follows: (1) Javanese identity is represented by the attitude of "nrimo", which means “accept”; (2) canting is a symbol of high culture which is defeated; (3) high culture must negotiate with mass culture in order to survive.